Supervision Of Buleleng District Health Office On The Implementation Of Empirical-Traditional Health Service And The Protection Of The Community’s Right To Health - Karlina Sumiari Tangkas; Endang Wahyati Yustina; Daniel Budi Wibowo (SOEPRA, 2018)
Empirical-traditional health service existing in Bali Province, especially in Buleleng District, was growing rapidly. Therefore, it was necessary to monitor the implementation of traditional health services in Buleleng District. The purpose of this study was to know the supervision conducted by Buleleng District Health Office on the implementation of empirical-traditional health service and the protection of the community’s right to health. This study used socio-legal approach having an analytical-descriptive specification and qualitative research design. Data gathering was conducted by having in-depth interviews. The results of the study showed about the legal basis of empirical-traditional health service, implementation of supervision to the Head of Buleleng District’s Health Office and The factors influencing the implementation of the supervision. The conclusions that could be drawn was the supervision conducted by the Buleleng District’s Health Office was not optimal so that the community’s health rights had not been protected. It was suggested that the provincial government, the empirical-traditional health service providers, and the community as well would push Buleleng District’s Health Office to perform better supervision so that it would be able to provide protection for the community’s rights to health